Kompetensi Organisasi dan Budaya Inovasi (Studi pada Perguruan Tinggi Swasta Di Kopertis V Yogyakarta) - ., Winarno (Universitas Brawijaya, Indonesia, 2012)
The objectives of this study are to examine and analize the influence of human capital and organizational learning on organizational performance mediated by organizational competence and innovation culture.The population of this study was all of the private Higher Education who had 50% of accredited study programs, as many as 68 PTS, 15 PTS used to instrument test.The sampling technique used is sencus method as many as 53 PTS. Testing model uses structural equation modeling (SEM) with Partial Least Square (PLS) Approach. Result of the study show that 1) the intellectual capital to constitute primal indicator of human capital had significant influence on organizational performance mediated by organizational competence. 2) the intellectual capital to constitute primal indicator of human capital had significant influence on organizational performance mediated by innovation culture. 3) Personal's skills constitute primal indicator of organization learning had significant influence on organizational performance mediated by organizational competence. 4) Personal's skills constitute primal indicator of organization learning had significant influence on organizational performance mediated by innovation culture.